Capturing temporal shifts in forest soil-atmosphere feedbacks: evidence from a Mediterranean catchment - Ilenia Murgia; Christian Massari; Matteo Verdone; Konstantinos Kaffas; David Labat; Daniele Penna (Journal of Hydrology, 2026)

LuKARS 3.0: a high-performance computing software to model flow and transport processes in karst aquifers - Beatrice Richieri; Vianney Sivelle; Andreas Hartmann; David Labat; Muhammad Muniruzzaman; Gabriele Chiogna (Environmental Modelling & Software, 2025)

Evaluation of precipitation products for small karst catchment hydrological modeling in data-scarce mountainous regions - Ibrahim Al Khoury; Laurie Boithias; Vianney Sivelle; Ryan T. Bailey; Salam A. Abbas; Paolo Filippucci; Christian Massari; David Labat (Journal of Hydrology, 2024)

On the value of hydrochemical data for the interpretation of flow and transport processes in the Baget karst system, France - Beatrice Richieri; Daniel Bittner; Vianney Sivelle; Andreas Hartmann; David Labat; Gabriele Chiogna (Hydrogeology Journal, 2024)
Continuous hourly time series of hydrochemical data can provide insights into the subsurface dynamics and main hydrological processes of karst systems. This study investigates how high-resolution hydrochemical data can be used for the verification of robust conceptual event-based karst models. To match the high temporal variability of hydrochemical data, the LuKARS 2.0 model was developed on an hourly scale. The model concept considers the interaction between the matrix and conduit components to allow a flexible conceptualization of binary karst systems characterized by a perennial spring and intermittent overflow as well as possible surface water bypassing the spring. The model was tested on the Baget karst system, France, featuring a recharge area defined by the coexistence of karst and nonkarst areas. The Morris screening method was used to investigate parameter sensitivity, and to calibrate the model according to the Kling-Gupta Efficiency (KGE). Model verification was performed by considering additional hydrochemical constraints with the aim of representing the internal dynamics of the systems, i.e., water contributions from the various compartments of the conceptual model. The hydrochemical constraints were defined based on high-temporal resolution time series of SO 4 2− and HCO 3 − . The results of this study show that the simulation with the highest KGE among 9,000 model realizations well represents the dynamics of the spring discharge but not the variability of the internal fluxes. The implementation of hydrochemical constraints facilitates the identification of realizations reproducing the observed relative increase in the flow contribution from the nonkarst area.

Impact of land-use change on karst spring response by integration of surface processes in karst hydrology: The ISPEEKH model - Ibrahim Al Khoury; Laurie Boithias; Ryan T. Bailey; Chloé Ollivier; Vianney Sivelle; David Labat (Journal of Hydrology, 2023)

Toward the estimation of the transfer coefficient in karst systems: Using baseflow recession coefficient under matrix-restrained flow regime - Malihe Shirafkan; Zargham Mohammadi; Alireza Kavousi; Vianney Sivelle; David Labat; Thomas Reimann (Journal of Hydrology, 2023)

Short-term variations in tracer-test responses in a highly karstified watershed - Vianney Sivelle; David Labat (Hydrogeology Journal, 2019)

Hydroclimatic change disparity of Peruvian Pacific drainage catchments - Pedro Rau; Luc Bourrel; David Labat; Frédéric Frappart; Denis Ruelland; Waldo Lavado; Boris Dewitte; Oscar Felipe (Theoretical and Applied Climatology, 2018)

Rainfall along the coast of Peru during strong El Niño events - Janeet Sanabria; Luc Bourrel; Boris Dewitte; Frédéric Frappart; Pedro Rau; Olimpio Solis; David Labat (International Journal of Climatology, 2018)
While, climatologically, most areas of the Peruvian Pacific region do not experience precipitation, they can be affected by heavy rain and flooding during strong El Niño events with severe socio‐economic impacts. Only four strong El Niño events took place within the last five decades (1972/1973, 1982/1983, 1997/1998 and 2015/2016) which led to significant rainfall events in the northern part of Peru. Here a detailed analysis of the evolution of precipitation during these events was performed using gauge records from 1964 to 2016 from a network of 145 meteorological stations located along the Peruvian Pacific region. Through empirical orthogonal function analysis, the rainfall anomalies variability is interpreted as resulting from the combination of a meridional see‐saw mode (North–South) (Ep mode) and a zonal see‐saw mode (East–West) (Cp mode) that represent, respectively, 34 and 21% of the explained variance. It is shown that the extreme 1982/1983 and 1997/1998 El Niño events have a dominant projection on the Ep mode that has a strong loading in the northern region, while the 1972/1973 and 2015/2016 El Niño events have a relatively weak projection onto the Ep mode (about ten times less at the peak rainy season than the extreme events) and mostly project onto the Cp mode. Also, it is shown that while all events are associated with positive rainfall anomalies in the northern part of Peru which is accounted for by the Ep mode, the evolution of rainfall anomalies along the Cp mode exhibits a significant dispersion. This suggests that the impact of strong El Niño events on the highlands along the coast cannot solely be inferred from the magnitude of the sea surface temperature anomalies in the central equatorial Pacific. Overall, our study illustrates the nonlinearity of the ENSO teleconnection on the rainfall along the coast of Peru during strong El Niño events.

Evidence for deterministic chaos in long-term high-resolution karstic streamflow time series - David Labat; B. Sivakumar; A. Mangin (Stochastic Environmental Research and Risk Assessment, 2016)

Basin-scale analysis of rainfall and runoff in Peru (1969–2004): Pacific, Titicaca and Amazonas drainages - Waldo Sven Lavado Casimiro; Josyane Ronchail; David Labat; Jhan Carlo Espinoza; Jean Loup Guyot (Hydrological Sciences Journal, 2012)